Assessment Of Entrepreneurship Education As A Tool For Self-Reliance In Colleges Of Education In Adamawa State, Nigeria - USMAN, Ahmed; Thomas, K.; Gambo, I (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
The study assessed entrepreneurship education as a tool for self-reliance in Colleges of Education in Adamawa state, Nigeria. It specifically determined the extent to which entrepreneurship education promote educational development, adequacy of resources and identified the constraints facing teaching and learning of entrepreneurship education. Multi-stage random sampling technique was used to sample the respondents in the college of education, where a sampled 106 was drawn. The data obtained were analyzed using mean, standard deviation, rating and lickrt scale. The results revealed that entrepreneurship education encourages students to join businesses (mean score =.62), promotes economic development (mean score =.58) and self-reliance (mean score =4.55). it further revealed that there were inadequate staff (mean score =1.23) teaching environment (mean score =1.19) and materials for learning were inadequate (mean score =1.24). the major constraints facing teaching and learning of entrepreneurship education were inadequate materials for learning (mean score =2.82), skilled personals (mean score =2.78) poor remunerative to staff concern (mean score =2.67) and poor funding (mean score =2.63) it was concluded that education focuses on the overall development of students and the entrepreneurial curriculum system lays the foundation for the overall improvement of students and the entrepreneurial ability. The study recommended both governmental and non-governmental organizations should provide support to the institutions through the provision of funds, facilities and equipment and internship /houseman ship after graduation in entrepreneurship course as students’ industrial work experience scheme programme for all students should be made